2019
DOI: 10.3389/fpsyg.2019.00053
|View full text |Cite
|
Sign up to set email alerts
|

Inhibited Endogenous H2S Generation and Excessive Autophagy in Hippocampus Contribute to Sleep Deprivation-Induced Cognitive Impairment

Abstract: Background and Aim: Sleep deprivation (SD) causes deficit of cognition, but the mechanisms remain to be fully established. Hydrogen sulfide (H2S) plays an important role in the formation of cognition, while excessive and prolonged autophagy in hippocampus triggers cognitive disorder. In this work, we proposed that disturbances in hippocampal endogenous H2S generation and autophagy might be involved in SD-induced cognitive impairment.Methods: After treatment of adult male wistar rats with 72-h SD, the Y-maze te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…LC3 (microtubule-associated protein light chain 3, MAP LC3) was the first autophagosome marker protein to be identified in mammals and is homologous to the yeast autophagy-related gene Atg8. Similar to previous studies, SD has been shown to cause excessive levels of autophagy and may be one of the causes of impairment of learning and memory (8,29,30).…”
Section: Discussionsupporting
confidence: 83%
“…LC3 (microtubule-associated protein light chain 3, MAP LC3) was the first autophagosome marker protein to be identified in mammals and is homologous to the yeast autophagy-related gene Atg8. Similar to previous studies, SD has been shown to cause excessive levels of autophagy and may be one of the causes of impairment of learning and memory (8,29,30).…”
Section: Discussionsupporting
confidence: 83%
“…The Y-maze experiment was performed due to the animals’ nature of showing a preference to explore novel locations rather than going back to a previously explored arm ( Mo et al, 2013 ; Yang et al, 2019 ). In the Y-maze, the spontaneous test was performed to determine spatial working memory.…”
Section: Resultsmentioning
confidence: 99%
“…Different hypotheses have been suggested for the impairment effect of SD on memory performance. A previous study has shown that SD impairs the rats’ performance in several memory tests, due to the induction of autophagy in the hippocampus (Yang et al, 2019). In the radial arm maze, SD disrupts memory performance via attenuating hippocampal antioxidant capacity (Alzoubi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%